2023
DOI: 10.1111/1365-2435.14434
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric responses of abundance and diversity of N‐cycling genes to altered precipitation in arid grasslands

Mengying Zhao,
Haihua Shen,
Yankun Zhu
et al.

Abstract: Precipitation changes exert a fundamental effect on the nitrogen (N) cycle in water‐limited grasslands. Soil microbes are essential drivers of N cycle, and the rates and their stabilities of interrelated N‐cycling processes are reflected by the abundance and diversity of N‐cycling genes. Yet, little is known about how altered precipitation affects the genes involved in the entire N‐cycling pathways. By combining a 6‐year precipitation manipulation experiment (−30%, ambient, +30%, +50%) with metagenomic sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…The model significance and predictor importance were verified using the rfUtilities and rfPermute packages in the R software, respectively ( Ju et al., 2023 ; Yuan et al., 2023 ). Structural equation modeling (SEM) was conducted using the R “piecewiseSEM” package to evaluate the direct and indirect relationships among yield per plant, root length density, root surface area density, specific root length, and root diameter ( Jing et al., 2023 ; Zhao et al., 2023b ).…”
Section: Methodsmentioning
confidence: 99%
“…The model significance and predictor importance were verified using the rfUtilities and rfPermute packages in the R software, respectively ( Ju et al., 2023 ; Yuan et al., 2023 ). Structural equation modeling (SEM) was conducted using the R “piecewiseSEM” package to evaluate the direct and indirect relationships among yield per plant, root length density, root surface area density, specific root length, and root diameter ( Jing et al., 2023 ; Zhao et al., 2023b ).…”
Section: Methodsmentioning
confidence: 99%
“…However, this is not always the case. Recent studies have reported diverse responses of soil N pools (Zhang et al., 2023; Zhao et al., 2023) and N processes (Elrys et al., 2024; Kou et al., 2018; Song et al., 2023) to increased aridity. Additionally, from the perspective of 15 N isotopes, soil N cycling under dry conditions is generally considered more open compared with that under wet conditions as many previous studies have demonstrated that soil δ 15 N values significantly decrease with increasing mean annual precipitation (MAP), both regionally (Brunello et al., 2024; de Freitas et al., 2015) and globally (Amundson et al., 2003; Craine et al., 2009).…”
Section: Introductionmentioning
confidence: 99%